A Pile of Shifts II: Structure and -Theory - Hebert, Shelley; Klimek, Slawomir; McBride, Matt; Peoples, J. Wilson (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
We discuss *-algebras associated with several different natural shifts on the Hilbert space of the -adic tree, continuing the analysis from [Banach J. Math. Anal. 19 (2025), 32, 30 pages, arXiv:2412.00854] and in particular, we describe their structure and compute the -theory groups.